AN ETHNOFORESTRY STUDY OF THE BADUY COMMUNITY’S INDIGENOUS KNOWLEDGE IN FOREST CONSERVATION AND WATER RESOURCE MANAGEMENT - Bakti, Iriana; Karimi, Reza; Rahimi, Ramin (Journal of Selvicoltura Asean, 2025)
The escalating global environmental crisis highlights the need for effective conservation models, a gap addressed by analyzing indigenous knowledge systems. This study’s objective was to investigate and analyze the ethnoforestry principles and practices of the Baduy community in Banten, Indonesia, focusing on their contribution to the sustainable conservation of forests and water resources. Employing a qualitative ethnographic approach, data were gathered in Kanekes village through in-depth interviews with customary leaders (Pu’un), participant observation, and documentation of customary laws (pikukuh). The findings reveal a sophisticated ethnoforestry system rooted in the pikukuh customary law, which strictly delineates forest zones into protected (leuweung kolot) and agricultural (huma) areas. This classification governs resource extraction and ensures the preservation of core ecosystem functions. Crucially, water management is intrinsically linked to forest protection, preserving the Ciujung watershed’s quality. The novelty lies in empirically documenting this successful indigenous system. The implication is that the Baduy’s integration of spiritual beliefs with ecological principles offers a proven, replicable model for sustainable development, underscoring the vital importance of incorporating local wisdom into contemporary environmental governance and policy-making.